2021
DOI: 10.3389/fnut.2021.707763
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Colon Fermentation of Soluble Arabinoxylan Is Modified Through Milling and Extrusion

Abstract: Dietary fibers such as arabinoxylan (AX) are promising food constituents to prevent particular diet-related chronic diseases because of their prebiotic properties. Arabinoxylan fermentation by the gut microbiota depends on the structural architecture of AX, which can be modified during food processing and consequently affect its prebiotic potential, but it is little investigated. Therefore, the aim of this study was to evaluate the effects of naturally occurring and processing-induced structural alterations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…Correlated to the SEM micrographs in Figure 2, the loose, porous, and rough surface may provide a higher chance of being utilized by the bacteria [65]. Evidence can be found in the results reported by Demutu et al that extruded and milled WBAX stimulated faster Bifidobacteria growth than the native control [70]. Next, we investigated the prebiotic potential of co-modified BWB by evaluating the abundance of Bifidobacterium and Lactobacillus using simulated intestinal fermentation.…”
Section: Inulin Bwb and Co-modified Bwb Fermentation Increase The Rel...mentioning
confidence: 77%
See 2 more Smart Citations
“…Correlated to the SEM micrographs in Figure 2, the loose, porous, and rough surface may provide a higher chance of being utilized by the bacteria [65]. Evidence can be found in the results reported by Demutu et al that extruded and milled WBAX stimulated faster Bifidobacteria growth than the native control [70]. Next, we investigated the prebiotic potential of co-modified BWB by evaluating the abundance of Bifidobacterium and Lactobacillus using simulated intestinal fermentation.…”
Section: Inulin Bwb and Co-modified Bwb Fermentation Increase The Rel...mentioning
confidence: 77%
“…Correlated to the SEM micrographs in Figure 2 , the loose, porous, and rough surface may provide a higher chance of being utilized by the bacteria [ 65 ]. Evidence can be found in the results reported by Demutu et al that extruded and milled WBAX stimulated faster Bifidobacteria growth than the native control [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…78 In addition, the fermentation behavior of soluble AX in wheat bran and rye flour in the human colon in vitro is closely related to the factors of extrusion, grinding, molecular weight, arabinose/xylan ratio and bound phenolic acids. 79 In vitro fermentation experiments with different genotypes of maize bran AX demonstrated that both the SCFA profile and gut microbiota were altered in a genotype-specific manner, further indicating that fiber structure is highly specific for the gut bacteria to utilize and produce SCFAs. 80 In addition, oat-derived and barley-derived β-glucans yield opposite results in regulating the abundance of intestinal Bifidobacteria in participants of different ages, 81,82 and even the same intervention in similar populations shows interindividual differences in the modulation of the gut microbiota composition, possibly owing to interindividual factors such as baseline microbiota composition and diet.…”
Section: Metabolism Of Df and Pps And Their Effects On The Gutmentioning
confidence: 99%
“…In vitro human gut microbiota models inoculated with fecal microbiota and mimicking the physicochemical conditions of the gut are powerful tools to evaluate the xenobiotic-microbiota interactions [10,11]. We previously showed that the artificial microbiota produced with the PolyFermS model inoculated with immobilized fecal microbiota is a reproducible source of large amounts of inocula for high throughput testing and comparison of different treatment conditions, including xenobiotic degradation with the same microbiota background [10,12]. A particular advantage of using the latter is that the amount of inoculum is not limiting and high inoculation ratios (e.g.…”
Section: Introductionmentioning
confidence: 99%